In Vitro Micropropagation of Anisochilus carnosus (L) Wall - N. A. Reshi, M. S. Sudarshana, H. V. Girish (Journal of Applied Pharmaceutical Science, 2017)
The present study describes a protocol for the in vitro mass propagation of Anisochilus carnosus (L) Wall – an anticancer ethnomedicinal herb. Young and healthy leaf segments were inoculated on to the solid Murashige and Skoog (MS) medium supplemented with different auxins and cytokinins individually and in combination. Maximum callusing percentage (97%) was achieved in MS medium fortified with 2,4-Dichlorophenoxyacetic acid (2,4-D) at 5 mg/l. Multiple shoots were achieved in benzylaminopurine (BAP) and Indole-3 acetic acid (IAA) combination with maximum of 14±0.23 shoots per culture at 7 mg/l BAP + 3.5 mg/l IAA concentration. For in vitro rhizogenesis, elongated micro shoots were aseptically excised and transferred to the half strength MS liquid medium enriched with different auxins. Out of the different auxins tested, indole butyric acid (IBA) was found to be the best for rhizogenesis at 2 mg/l with maximum of 11±0.45 roots per shoot. The well established rooted plantlets were hardened under laboratory conditions for two weeks by transferring to the poly cups containing vermicompost and sterile soil in the ratio of 1:1. The hardened plantlets were transferred to the green house for two weeks and finally to the filed with 90 % survivability.
Keywords: Leaf segments, Callusing, Multiple shoots, Rhizogenesis, Acclimatisation, A. carnosus.